Experiences, challenges, and enablers for promoting interprofessional education among medical students: A scoping review - Maxwell Ateni Assibi; Bruce Ayabilla Abugri; Patience Afua Adwaapa Karikari; Shamsu-Deen Ziblim; Victor Mogre (PLoS ONE, 2026)
Background Interprofessional education (IPE) has been commonly employed to facilitate preparation for collaborative practice among medical students. However, differences in IPE implementation and a lack of synthesis of student experiences continue to influence its integration into medical education. Methods The scoping review was conducted following the Arksey and O’Malley guidelines and was reported according to the PRISMA-ScR extension. Electronic databases such as PubMed, Scopus, and Web of Science were searched to include studies published between 2014 and 2024. The search yielded eight studies that met the inclusion criteria for this review. The results were synthesized to explore students’ experiences, challenges, and facilitators regarding IPE. Results The review found that medical students generally reported having a positive orientation towards collaborative practice and valued the opportunity to learn with others. However, understanding of professional roles was more inconsistent. Identified challenges included ambiguity of roles, hierarchy of professions, and constraints of time and organization. Enablers included integration into the curriculum, learning in practice, interaction and support. Conclusion IPE facilitates learning in collaborative practice, and its effectiveness relies on its development and implementation. Further consideration should be given to role clarification, learning, and integration in medical education programs. Future research should focus on the long-term effects of IPE on professional practice.